Persistent circulating unmetabolised folic acid in a setting of liberal voluntary folic acid fortification. Implications for further mandatory fortification? - Bailey Steven W; Daly Sean; Traynor Aisling; Daly Leslie; Staines Anthony; Sweeney Mary R; Alverson Patricia B; Ayling June E; Scott John M (BMC, 2009)
Abstract Background Ireland is an example of a country that has extensive voluntary fortification with folic acid. After a public consultation process, in 2006, the Food Safety Authority in Ireland FSAI <abbrgrp>1</abbrgrp> recommended mandatory fortification. However due to safety considerations this decision is now on hold. Before mandatory fortification goes ahead, existing levels of unmetabolised folic acid and their anticipated increase after fortification needs investigation because of the potential of folic acid to mask pernicious anaemia and possibly accelerate the growth of existing cancers. The aim of this study was to examine the levels of circulatory unmetabolised folic acid in Irish adults (both fasted and un-fasted) and new-born infants (fasted) before the proposed implementation of mandatory folic acid fortification. A secondary aim was to predict the increase in circulatory unmetabolised folic acid levels after fortification. Methods Study 1. Setting: Irish Blood Transfusion Service (IBTS). Whole blood samples were collected from blood donors (n = 50) attending for routine blood donation sessions (representing the general population). Subjects were not fasted prior to sampling. Study 2. Setting: Coombe Women's and Infant's University Hospital, Dublin. Whole blood samples were collected by venipuncture from mothers (n = 20), and from their infant's umbilical-cords (n = 20) immediately after caesarean section. All women had been fasted for at least 8 hours prior to the surgery. A questionnaire on habitual and recent dietary intakes of folic acid was administered by an interviewer to all subjects. The data collection period was February to April 2006. Serum samples were analysed for plasma folate, plasma folic acid and red cell folate. Results Blood Donor Group: Circulatory unmetabolised folic acid was present in 18 out of 20 mothers (fasted) (CI: 68.3%-99.8%) comprising 1.31% of total plasma folate, 17 out of 20 babies (fasted) (CI: 62.1%-96.8%), and 49 out of 50 blood donors (unfasted) (CI: 88.0%-99.9%), comprising 2.25% of total plasma folate, Conclusion While the levels of circulatory unmetabolised folic acid reported are low, it is persistently present in women immediately after caesarean section who were fasting indicating that there would be a constant/habitual exposure of existing tumours to folic acid, with the potential for accelerated growth. Mandatory fortification might exacerbate this. This has implications for those with responsibility for drafting legislating in this area.